Representation of Electric Power Systems by Complex Networks with Applications to Risk Vulnerability Assessment (2015)
The occurrence of impact events (e.g. blackouts with vast geographic coverage) into electrical critic infrastructure systems usually require the analysis of cascade failure root causes through the conduction of structural vulnerability studies, with well-defined methodologies that may guide decision-making for implementation of preventing actions and for operation recovering into the power system (e.g. N-1 and N-t contingency studies). This technical contribution provides some alternative techniques based upon complex networks and graph theory, which in the last few years have been proposed as useful methodologies for analysis of physical behavior of electric power systems. Vulnerability assessment is achieved by testing their performance into random risks and deliberate attacks threats scenarios. Results shown in this proposal lead to conclusions on the use of complex networks for contingency analysis by means of studies of those events that result in cascade failures and consumer disconnections.